Intramolecular [2+2] Cycloaddition of N‐Allylcinnamamines and N‐Allylcinnamamides by Visible‐Light Photocatalysis. Issue 1 (27th November 2019) - Oderinde, Martins S.; Kempson, James; Smith, Daniel; Meanwell, Nicholas A.; Mao, Edna; Pawluczyk, Joseph; Vetrichelvan, Muthalagu; Pitchai, Manivel; Karmakar, Ananta; Rampulla, Richard; Li, Jianqing; Murali Dhar, T. G.; et al.
Abstract : The visible light‐promoted intramolecular [2+2] cycloaddition of N ‐allylcinnamamines and N ‐allylcinnamamides in the presence of catalytic amounts of [IrdF(CF3 )ppy2 (dtbpy)]PF6 is reported. Low energy visible light and a high triplet energy iridium‐photosensitizer were efficient at promoting the cycloaddition reaction of N ‐allylcinnamamides and N ‐allylcinnamamines to the corresponding aryl‐3‐azabicyclo[3.2.0]heptanones and aryl‐3‐azabicyclo[3.2.0]heptanes, respectively, with high diastereoselectivity and under mild conditions. Azabicyclic fused rings have been employed as surrogates for piperidine motifs in drug discovery. Functional groups useful for deployment and/or elaboration in drug discovery campaigns were all shown to be tolerated, including halides, CF3, cyanide, ester, acetamide, acetate, CH3 O, pyridyl, furan, carbamate, tosyl, benzyl, and benzoate. Abstract : Visible light‐promoted intramolecular [2+2] cycloaddition of N ‐allylcinnamamines and N ‐allylcinnamamides in the presence of catalytic amounts of [IrdF(CF3 )ppy2 (dtbpy)]PF6 is reported. Low energy visible light and a high triplet energy iridium‐photosensitizer were efficient at affording the corresponding aryl‐3‐azabicyclo[3.2.0]heptanones and aryl‐3‐azabicyclo[3.2.0]heptanes, respectively.